Pelaksanaan Bantuan Hukum Cuma-Cuma bagi Masyarakat Kurang Mampu di Indonesia: Studi Empiris dan Analisis Implementasi Undang-Undang No. 16 Tahun 2011 (Lembaga Pengembangan Kinerja Dosen, 2025)
Legal aid is a constitutional right of the poor to obtain free access to justice. Law No. 16 of 2011 regulates the provision of legal aid by legal aid institutions and advocates. This study uses a juridical-empirical approach to analyze the implementation of legal aid in Indonesia, especially in remote areas, by identifying obstacles and opportunities for increasing access to legal aid. The results of the study indicate that the limitations of legal aid institutions in rural areas, low legal literacy of the community, and limited funding are the main obstacles. Strategic recommendations include strengthening village-based legal service centers and increasing the socialization of legal aid.